2010
DOI: 10.1007/s10237-010-0243-5
|View full text |Cite
|
Sign up to set email alerts
|

Micromechanics of diffuse axonal injury: influence of axonal orientation and anisotropy

Abstract: Multiple length scales are involved in the development of traumatic brain injury, where the global mechanics of the head level are responsible for local physiological impairment of brain cells. In this study, a relation between the mechanical state at the tissue level and the cellular level is established. A model has been developed that is based on pathological observations of local axonal injury. The model contains axons surrounding an obstacle (e.g., a blood vessel or a brain soma). The axons, which are des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(66 citation statements)
references
References 44 publications
0
66
0
Order By: Relevance
“…In a previous study (Cloots et al 2011), it was shown that anisotropy at the tissue level causes the strains to become smaller in the main axonal direction, but larger in other directions for the same stress levels. For a homogeneous axonal alignment (e.g., without the presence of an inclusion), this would also lead to reduced axonal strains, even for the higher strain levels in other directions than the main axonal direction, since then the loading direction is not aligned with the axons anymore.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…In a previous study (Cloots et al 2011), it was shown that anisotropy at the tissue level causes the strains to become smaller in the main axonal direction, but larger in other directions for the same stress levels. For a homogeneous axonal alignment (e.g., without the presence of an inclusion), this would also lead to reduced axonal strains, even for the higher strain levels in other directions than the main axonal direction, since then the loading direction is not aligned with the axons anymore.…”
Section: Discussionmentioning
confidence: 92%
“…By means of the Macaulay brackets · , the fibers contribute only in tension and not in compression, as Ẽ becomes 0 ifẼ is negative. The fiber contribution to the stiffness is assumed linear (i.e., k 2 → 0) (Cloots et al 2011). Viscoelasticity is added by using:…”
Section: Head Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…A value of 1214 Pa is assigned to the shear modulus G while 11 590 Pa is assigned to the mechanical parameter k 1 in respect of the ratio of 0.105 experimentally identified by Ning et al [20]. A value of 0 is chosen for k 2 as the fibre contribution to the stiffness is assumed to be linear [30]. The bulk modulus K, even though experimental observations show that its magnitude is around 2.1 GPa, is instead assigned a value of 50 MPa to prevent volumetric locking of the elements during the FE simulation.…”
Section: Anisotropic Hyperviscoelastic Formulationmentioning
confidence: 99%